The Significance of Decentralisation and of Governance Quality for the Regional Development and the Absorption of the European Funds - LUPANCESCU, Mihaela; AXINTE, Gheorghe; SERBAN, Razvan; CIOBOATĂ, Marian (Journal of Advanced Research in Management, 2020)
In Romania the significance of the administrative traditions and of the political management and the slow pace of the reforms from the public sector affected the development potential of some strong institutions. In consequence, 30 years from the fall of the communist system we can explain the weak management of the external aid referring to the socio-political circumstances and the weak institutions offering a significant handicap for Romania in this sense. Despite these, the strong variation among the countries in Central and Eastern Europe is still a problem to be identified referred to the global absorption of the funds from the point of view of the causes. Studying the way in which the administrative capacity can interact with the internal governance and the institutional and regional arrangements became an important field of study in order to understand the performance problems. Assessing the flow of ideas about the institutional and administrative effort for a new region, we pointed out the fact that this is useless if it not accompanied by a decentralization. Therefore, the regions should not get the attributions of the centre, so that the main purpose of a new organization on regions to be decentralization and not only mapping new entities comprising a vaster territory than the one of the counties. The hypothesis we start from in our research is that the political and the administrative spheres impacts the various stages of the absorption process. Understanding the way in which the specific aspects of absorbing the EU funds might interact with the internal political factors helps us understand the way in which this influences the administrative capacity.